Slipping Through the Cracks in e-Lexicography. (28th November 2020) - Frankenberg-Garcia, Ana; Rees, Geraint Paul; Lew, Robert
Abstract: Despite the remarkable advances made in recent years to facilitate the lexicographer's work of interpreting and synthesizing the complexity of language uncovered by corpora, an uncritical use of cutting-edge corpus tools and resources can instill a false sense of assurance. In this paper, authentic examples pertaining to wordlist use, collocation research and example selection that arose when compiling a real-world lexical database are discussed through the lens of problems that can easily slip through the cracks in e-lexicography. In doing so, we emphasize the importance of solid training and sound lexicographic judgment when using corpora, corpus tools and corpus-derived resources, and provide an opportunity to reflect on how e-lexicography can be further refined in the future.